Classification of affective and social behaviors in public interaction for affective computing and social signal processing - Konstantinova,Maria; Kazimirova,Evdokia; Perepelkina,Olga (PeerJ Preprints, 2018)
There are numerous models for affective states classification and social behavior description. Despite proving their reliability, some of these classifications turn out to be redundant, while others — insufficient for certain practical purposes. In this paper we propose a classification describing human behavior in the course of public interaction. We relied on existing literature to adopt the current achievements to a practical task---to automatically detect various aspects of human behavior. Our goal was not to suggest a new universal model describing human behavior, but to create a quite comprehensive list of affective and social behaviors in public interaction. The final list consists of the following seventeen scales: happiness, surprise, anxiety, anger, sadness, disgust, shame, pride, contempt, admiration, self-presentation, self-disclosure, mental effort, friendliness, engagement, pleasure and self-confidence. These scales concern only behavior patterns which can be observed by outside annotator and do not include personal traits or hidden states.
Keywords: affective states; social behavior; affective computing; social signal processing; public interaction; emotions